The challenge of aging and pharmacoterapeutic complexity in the HIV + patient - Ramón Morillo-Verdugo; José Ramón Blanco Ramos; Laila Abdel-Kader Martín; María Álvarez de Sotomayor (Elsevier, 2018)
Objective: To describe the current knowledge and management of aging and pharmacotherapeutic complexity in HIV + patients. Method: A review of literature was carried out, including articles, originals or reviews, published in English or Spanish, from 2007 to 2017, which analysed the aging and pharmacotherapeutic complexity in HIV + patients. The terms «Polypharmacy»/»Polypharmacy», «Aging»/»Aging», «Frailty»/»Fragility», «Pharmacotherapeutic Complexity»/»Medication Regimen Complexity» and «HIV»/"HIV» were combined. The review was carried out independently by two authors. The degree of agreement, according to the Kappa index, was analysed. Results: A total of 208 references were analysed, including, finally, only 68. An aging of the population and an increase in associated comorbidities have been identified, especially over 50 years-old. Immunological changes similar to those that are generated in a non-infected elderly population have been described. These conditions influencing the prescription of antiretroviral treatment, according to studies identified. In parallel, polypharmacy is increasingly present, being defined exclusively by the concomitant use of five drugs. Pharmacotherapeutic complexity, through the Medication Regimen Complexity Index, has begun to analyse and relate to health outcomes. There has been a need to know and apply concepts already known in non-HIV-aged population, such as de-prescription, potentially inappropriate medication, cholinergic risk, although few results are available. Conclusions: There is a growing interest to know about the relationship between HIV and aging. Pharmacotherapeutic complexity is beginning to be used as a pharmacotherapeutic follow-up criterion due to its influence on health outcomes. It is necessary to manage and incorporate new concepts that help pharmacotherapeutic optimization in this population